The Roman Curia and spiritual welfare of migrants - NECEL, WOJCIECH (Prawo Kanoniczne, 2013)
From its beginning, the Church offered pastoral care to all categories of migrants and itinerant people, as well as establishing responsibility for this specific action across all levels of her structure. John Paul II, in his apostolic constitution Pastor Bonus announced on the 28th June 1988, adjusted the work and structure of the Roman Curia to the actual pastoral needs of the Church. According to this document, all the issues concerning migrants are the specific responsibility of the Pontifical Council for the Pastoral Care for Migrants and Itinerant People. Reflecting on the various dicasteries it is necessary to note that as each of them undertake their particular responsibilities, they also play a role and participate in the apostolate for people who are on the move.